Updated checklist of the mosquitoes (Diptera: Culicidae) known to occur in Iran, with updated keys to the genera, subgenera and species of Aedes - Azari-Hamidian, Shahyad; Harbach, Ralph E. (Zootaxa, 2025)
The list of mosquitoes (Diptera: Culicidae) found in Iran is updated to include new country records, and keys are provided to identify the adult females and fourth-instar larvae to subfamily and genus. Keys are also provided to identify the adult females and fourth-instar larvae of Aedes to subgenus and species. New additions to the keys, which constitute a supplement to the keys of Azari-Hamidian & Harbach (2009), include Aedes cinereus, Ae. unilineatus, Mansonia uniformis and Orthopodomyia pulcripalpis, which were recently recorded in the country, and Ae. asiaticus, which was previously recognized as a subspecies of Ae. pulcritarsis. Seventy-three species representing eight genera are now known to occur in Iran.